Immunogenicity of Tetravalent Protein Vaccine SCTV01E-2 against SARS-CoV-2 EG.5 Subvaraint: A Phase 2 Trial - Jihai Tang; Qinghua Xu; Chaoyin Zhu; Kun Xuan; Tao Li; Qingru Li; Xingya Pang; Zhenqiu Zha; Jinwei Li; Liyang Qiao; Haiyang Xu; Gang Wu; et al. (Vaccines, 2024)
The Omicron EG.5 lineage of SARS-CoV-2 is currently on a trajectory to become the dominant strain. This phase 2 study aims to evaluate the immunogenicity of SCTV01E-2, a tetravalent protein vaccine, with a specific emphasis on its immunogenicity against Omicron EG.5, comparing it with its progenitor vaccine, SCTV01E (NCT05933512). As of 12 September 2023, 429 participants aged ≥18 years were randomized into the groups SCTV01E (N = 215) and SCTV01E-2 (N = 214). Both vaccines showed increases in neutralizing antibody (nAb) against Omicron EG.5, with a 5.7-fold increase and a 9.0-fold increase in the SCTV01E and SCTV01E-2 groups 14 days post-vaccination, respectively. The predetermined statistical endpoints were achieved, showing that the geometric mean titer (GMT) of nAb and the seroresponse rate (SRR) against Omicron EG.5 were significantly higher in the SCTV01E-2 group than in the SCTV01E group. Additionally, SCTV01E and SCTV01E-2 induced a 5.5-fold and a 5.9-fold increase in nAb against XBB.1, respectively. Reactogenicity was generally mild and transient. No vaccine-related serious adverse events (SAEs), adverse events of special interest (AESIs), or deaths were reported. In summary, SCTV01E-2 elicited robust neutralizing responses against Omicron EG.5 and XBB.1 without raising safety concerns, highlighting its potential as a versatile COVID-19 vaccine against SARS-CoV-2 variants.